15O-water PET perfusion in complex congenital heart disease - Kettunen, Sanna; Paakkanen, Riitta; Ojala, Tiina; Maaniitty, Teemu; Uusitalo, Valtteri (Oxford University Press (OUP), 2026)
Aims
Positron emission tomography (PET) perfusion with 15O-water is the reference standard for myocardial blood flow (MBF) quantification. Its strengths are low radiation dose, optimal tracer kinetics, and a short imaging protocol. However, the use of 15O-water or PET perfusion in patients with various complex congenital heart diseases has been rarely studied. We report the initial experiences of 15O-water PET perfusion in these patients.
Methods and results
All 15O-water scans from patients with complex congenital heart disease at Helsinki University Hospital were retrospectively assessed (11/2021–11/2025). Thirteen congenital heart disease patients who underwent adenosine-stress 15O-water PET were identified. Most common diagnoses were transposition of the great arteries (5/13, 38%), Tetralogy of Fallot (3/13, 23%), and univentricular heart (3/13, 23%). PET perfusion was diagnostic in all cases with no adverse effects reported. The radiation dose for stress protocol was 0.3 mSv for paediatric and 0.6 mSv for adult patients, and double when rest perfusion was also obtained to calculate myocardial flow reserve. The global stress MBF was normal (>2.3 mL/g/min) in 12/13 patients. Eleven patients (85%) had anatomical coronary imaging available, all without significant stenoses. One patient had an apical transmural scar on cardiac magnetic resonance imaging, and both stress and rest 15O-water PET perfusion was decreased.
Conclusion
15O-water PET offers a feasible and safe ultra-low-dose approach to quantify myocardial perfusion in complex congenital heart disease and may help identify flow-limiting disease when CT anatomy alone is inconclusive.